Studi Kontruksi dan Kegunaan Kabel Photovoltaik (PV) pada Sistem Pembangkit Listrik Tenaga Surya Berbasis On-Grid di Gedung BNI Tower PIK 2 - Sudarmanto Sudarmanto; Sulistyo Widodo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Solar Photovoltaic (PV) Power Plants have become one of the most promising renewable energy technologies to support sustainable energy development. In PV systems, photovoltaic (PV) cables function as the primary conductors for transmitting direct current (DC) electrical energy from solar modules to the inverter; therefore, their selection and installation must comply with applicable technical standards. This study aims to analyze the construction, characteristics, and applications of PV cables in the On-Grid Solar Power Plant installed at BNI Tower PIK 2. The research employed a field case study using descriptive and quantitative approaches through direct observation, voltage, current, and cable temperature measurements, as well as DC voltage drop analysis. The results indicate that the HI Z2Z2-K PV cable used in the system complies with IEC 62930:2017 standards and is constructed with tinned copper conductors and XLPO insulation, providing excellent resistance to high temperatures, ultraviolet radiation, humidity, and outdoor environmental conditions. The voltage drop calculations show that all measured strings exhibit voltage losses below the recommended maximum limit of 3%, resulting in no significant impact on system performance. Furthermore, thermal measurements reveal that the cable operating temperature remains within safe limits without indications of overheating. The study concludes that the use of standard-compliant PV cables and proper installation methods significantly contributes to the efficiency, safety, and long-term reliability of On-Grid photovoltaic power generation systems.